Deyeuxia debilis (Poaceae, Agrostidinae): typification, taxonomy and update of the Chinese distribution - Paszko, Beata; Chen, Wen-Li; Szczepaniak, Magdalena (Phytotaxa, 2013)
The name Deyeuxia debilis (Poaceae, Agrostidinae), based on Calamagrostis debilis, is lectotypified by a specimen originating from India (Sikkim, Chola) in accordance with the original description and with the current use of the name by the majority of Indian and Chinese authors. The taxonomy of the species is clarified and discussed, especially in relation to the similar Deyeuxia moupinensis and D. gaoligongensis. An amended circumscription of D. debilis is given, together with an illustration of the spikelet and culm morphology. The distribution area of D. debilis includes India and China. The range of this species in China is extended as it is recorded for the first time from the Gaoligong Shan region of NW Yunnan, SW China. A key to distinguish D. debilis, D. gaoligongensis and D. moupinensis is provided.